Global Inflation - Matteo Ciccarelli; Benoît Mojon (Federal Reserve Bank of Chicago, 2008)
This paper shows that in ation in industrialized countries is largely a global phenomenon. First, the inflation rates of 22 OECD countries have a common factor that alone accounts for nearly 70 percent of their variance. This large variance share that is associated with Global Inflation is not only due to the trend components of inflation (up from 1960 to 1980 and down thereafter) but also to fluctuations at business cycle frequencies. Second, we show that, in conformity to the prediction of New Keynesian open economy models, there is little spillover of inflationay shocks across countries. The comovement of inflation comes largely from common shocks. Global Inflation is a function of real developments at short horizons and monetary developments at longer horizons. Third, there is a robust error correction mechanism that brings national inflation rates back to Global Inflation. A simple model that accounts for this feature consistently beats the previous benchmarks used to forecast inflation 4 to 8 quarters ahead across samples and countries.
Keywords: E31; E37; F42; 330; global Inflation; common factor; international business cycle; OECD countries; Inflation; Inflationsübertragung; Inflationskonvergenz; Globalisierung; OECD-Staaten